The role of LncRNA-mediated autophagy in cancer progression - Liu, Zi-yuan; Tang, Jia-ming; Yang, Meng-qi; Yang, Zhi-hui; Xia, Jia-zeng (Frontiers in Cell and Developmental Biology, 2024)
Long non-coding RNAs (lncRNAs) are a sort of transcripts that are more than 200 nucleotides in length. In recent years, many studies have revealed the modulatory role of lncRNAs in cancer. Typically, lncRNAs are linked to a variety of essential events, such as apoptosis, cellular proliferation, and the invasion of malignant cells. Simultaneously, autophagy, an essential intracellular degradation mechanism in eukaryotic cells, is activated to respond to multiple stressful circumstances, for example nutrient scarcity, accumulation of abnormal proteins, and organelle damage. Autophagy plays both suppressive and promoting roles in cancer. Increasingly, studies have unveiled how dysregulated lncRNAs expression can disrupt autophagic balance, thereby contributing to cancer progression. Consequently, exploring the interplay between lncRNAs and autophagy holds promising implications for clinical research. In this manuscript, we methodically compiled the advances in the molecular mechanisms of lncRNAs and autophagy and briefly summarized the implications of the lncRNA-mediated autophagy axis.